KAJIAN LITERATUR TENTANG INTEGRASI NILAI-NILAI EKONOMI SYARIAH DALAM KURIKULUM PENDIDIKAN ISLAM: KAJIAN LITERATUR TENTANG INTEGRASI NILAI-NILAI EKONOMI SYARIAH DALAM KURIKULUM PENDIDIKAN ISLAM - Zaky Mubarok; Fahmul Hikam Al Ghifari (LEMBAGA PENELITIAN DAN PENGABDIAN PADA MASYARAKAT, 2025)
The low level of Islamic economic literacy in Indonesia presents a significant challenge for Islamic education, given that the majority of the population is Muslim. This study aims to critically examine efforts to integrate the values of Islamic economics into the Islamic education curriculum through a qualitative descriptive approach based on literature review. Data were collected from various academic literature and official curriculum documents. The findings of the study indicate that values of Islamic economics such as justice, social responsibility, and anti-usury are highly relevant to be instilled in education. Integration strategies identified include an integrated curriculum, specialized subjects, contextual approaches, and Islamic extracurricular activities. However, the implementation of integration faces obstacles such as limited teacher competence, teaching materials, and national policy support. The conclusion of this study emphasizes the importance of education in shaping a Muslim generation that is not only religious but also has ethical and practical economic awareness.